INVENTARISASI ZOOPLANKTON UNTUK PAKAN ALAMI LARVA UDANG KARANG (PANULIRUS HOMARUS L.) DI TELUK WEDI OMBO, GUNUNG KIDUL, YOGYAKARTA - Trijoko Trijoko; Diana U.W. Pasaribu (Universitas Gadjah Mada, 2004)
The aim of the research was to know the diversity of zooplankton in Wedi Ombo Bay, Gunung Kidul, Yogyakarta, as candidates of live feed for spiny lobster (Panulirus homarus L.) larvae. Samples were collected from August 2002 to January 2003 by using Van Dorn tubes water sampler at 0 m, 5 m and 10 m of water depth for each sampling point. The zooplankton was identified to the genera level.The result showed that 8 subclass zooplankton compraised of 24 genera, i.e. 15 genera of Copepoda, 2 genera of Branchiopoda, 1 genera of Ostracoda, 1 genera of Polychaeta, 2 genera of Rotifera, 1 genera of Malacostraca, 1 genera of Heteropoda and 1 genera of Appendicularia were found in Wedi Ombo Bay. Calanus had the highest dominance with density of 479 /50 l (24.1%). This zooplankton was found in each depth of water. Acartia had the lowest dominance with density of 12/50 l (0,6%). Based on the opening mouth of P. homarus larvae (114 µm), it was found that the18 genera of zooplankton had sizes less than 114 µm which might be suitable for live feed of P. homarus larvae. However, 6 genera of zooplankton had sizes more than 114 µm which might be unsuitable for live feed of P. homarus larvae.Based on the abundance of zooplankton, the size of zooplankton and the opening mouth of spiny lobster larvae, the best candidates of zooplankton for live feed of P. homarus larvae were Calanus an holoplanktonic copepod and Brachionus, a Rotifera.